Understanding the Meanings and Factors Motivating Academic Fraud: Exploration in Accounting Students - Dephiena, Sukma (E-Jurnal Akuntansi, 2020)
The purpose of this research is to depict the understanding of academic fraud and to elaborate the motivation to the perpetrators. This research uses qualitative approach with doing phenomenology variation of qualitative research with interview and literature documentation as the data collection method. The result of this research reveals the academic fraud conducted by the accounting student in breaking the rules, the existence of fraud culture that make student doing the academic fraud, and the ambition that motivate students to do fraud. Therefore, ambition as the motivation factor which underlined the academic fraud can be reduced by increasing the supervising more than usual. In line with the result of research that hopefully can be more contribute in to academic institution for make a better methods to decreasing the number of cheater. Keywords: Academic Fraud; Student Ethics; Fraud Definition; Fraud Motivation.